Sociological Juridical Review of the Phenomenon of Online Begging Legislative Perspectives in Indonesia - Astuti, Findhi; Utari, Indah Sri (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The phenomenon of online begging is one of the negative impacts of social media use. Online beggars take advantage of public sympathy to enrich themselves by creating content that evokes pity, viral content, which will invite the public to help by giving gifts that can be exchanged for money. The action of online beggars is an act of exploitation carried out against oneself and others; this is contrary to Pancasila, namely, just and civilized humanity, because it can pollute human dignity. Firm action and strong rules are needed to deal with the phenomenon of online begging, so that there is no public thought to make this phenomenon a profession in the future. The study used a normative legal method with a statutory, conceptual, and case approach. The results of the study show that, First, characteristics and legal qualifications of the phenomenon of online begging online beggars create sympathy from the public and the perpetrators create a drama full of manipulation that has been neatly arranged and to be said to be an act of online begging, it must meet the elements of the act. Second, from the legal side, the phenomenon of online begging touches on Pasal 504, 333 Criminal Code of Indonesia, Pasal 27 ayat (3) of the Law of Number 11 of 2008 on Information and Electronic Transactions, and Circular of the Minister of Social Affairs Number 2 of 2023, however, these articles are not strong enough to be used as a reference for taking action against online beggars. From a social side, the act of online begging can change the work values ​​of society and create inequality. Third, evaluation and recommendations for handling the phenomenon of online begging require regulations that have permanent legal force and increase digital literacy for the community to distinguish between forms of content creators and actions that are indicated as online begging.